Design and Performance Horizontal Axis Wind Turbine Taper Type - Arfidian Rachman; Putri Pratiwi; Lucky Ashari (Jurnal Teknik Mesin (JTM), 2019)
The potential of wind energy in Indonesia is sufficient for the development of renewable energy based on wind turbine, because the average wind speed ranges from 3-12 m / s. The wind that blows is dominated by West, Southwest, and Northwest winds with speeds sometimes reaching 2.5 m / s to 20 m / s. The designed wind turbine is a Taper type blade where the comparison of the tip chord to the base is 1.3: 1, with a blade length of 1 m. Where the blades are designed to be able to spin in high-speed winds and to maximize the efficiency that can be obtained. The design result that the highest peak is 59% at TSR 7 and the blades start to spin in winds of 8.7 m / s and at winds of 12 m / s the power produced reaches 3255 watts.